ROCK inhibitors as emerging therapeutic candidates for sarcomas - Micuda, Stanislav; Rösel, Daniel; Ryska, Ales; Brábek, Jan (Current cancer drug targets, 2010)
Sarcomas are malignant mesenchymal tumors of variable aggressiveness characterized by a substantial invasive and metastatic potential. In this review we discuss current results of pharmacological targeting of Rho/ROCK signaling in tumor cells, and the growing evidence supporting the hypothesis that Rho/ROCK dependent amoeboid mode of invasion could play a substantial role in metastatic potential of cells of malignant tumors, particularly of sarcomas. We attempt to cover pharmacological, biological and pathological aspects of the problematic in a multidisciplinary manner, from the views of molecular biology to medical practice. We are presenting evidence that blockade of Rho/ROCK pathway decreases amoeboid tumor cell invasion in vitro and substantially attenuates tumor growth and metastasis in vivo. While ROCK inhibitors have been used for a long time in treatment of cardiovascular diseases, the potential use of ROCK inhibitors to treat cancer metastasis has been considered only very recently. We propose that determination of the invasion mode that prevails in a particular sarcoma tumor, together with appropriate use of Rho/ROCK inhibitors could significantly improve the effectiveness of sarcoma tumor treatment in the future.
Keywords: kinázy asociované s Rho; Cell Movement; Protease Inhibitors; Sarcoma; inhibitory proteas; Protein Kinase Inhibitors; signální transdukce; lidé; Cell Adhesion; Signal Transduction; inhibitory proteinkinas; rho-Associated Kinases; buněčná adheze; sarkom; pohyb buněk; Humans